Nephrotoxicity of Potassium Bromate and Ameliorating Role of Ruta chalepensis on kidney Weight and Some Biochemical Parameters of Male Rats - Mabroka Hamad; Eldurssi, Ibrahim; Ebtesam Gheth; Gasem Abdalla; Abdullah Algassi (AlQalam Journal of Medical and Applied Sciences, 2022)
Background and aims. Potassium bromate (KBrO3), used as food additive in the manufacturing of bread, is proven hazardous for the human health. Ruta chalepensis (R. chalepensis) is used in Mediterranean folk medicine to treat pulmonary conditions, for example tuberculosis, and to decrease swelling of the spleen, as well as outwardly to treat wounds. The present study aimed to investigate the protective and curative effect of R. chalepensis against KBrO3 toxicity on kidney weight and some biochemical parameters of male rats. Methods. Fifty male albino rats were divided into five groups. The first group served as control animals. The second group was administered R. chalepensis at an oral daily dose of 0.5 g/Animal for four weeks. The third group received KBrO3 at an oral daily dose of 100 mg/kg/b. w. for four weeks. The fourth group (protective group) administered with R. chalepensis alone for 2 weeks and followed by R. chalepensis in association with KBrO3 for 2 weeks. The fifth group (therapeutic group) was first given KBrO3 alone for 2 weeks and was secondly administered KBrO3 in association with R. chalepensis for 2 weeks. After 2nd and 4th weeks of treatment, the determination of kidney weights and relative kidney weight were calculated. Also, the sera were collected for biochemical assays. Results. The results of the present study showed significant increase in the mean kidney weight in KBrO3 group at 2 weeks and therapeutic groups at 2 and 4 weeks compared to the control group. In addition, significant increase in relative kidney weight in KBrO3 group after 2 and 4 weeks, and therapeutic group after 2 weeks. While, there was decrease in relative kidney weight in R. chalepensis group after 4 weeks. Furthermore, serum urea levels significantly increased after 2 weeks in KBrO3 and therapeutic groups. A significant increase in serum urea levels showed in all groups except R. chalepensis group, which revealed a slight decrease after 4 weeks. No changes in serum creatinine levels in all groups after 2 weeks. In contrast, protective and therapeutic groups revealed significant elevation in serum creatinine levels after 4 weeks. Conclusion. It may be concluded the toxic effects of KBrO3 on kidneys and minimal ameliorative effects of R. chalepensis.